Perbedaan Kualitas Pelayanan KIA pada Program BPJS terhadap Kepuasan Pasien di Derah Perkotaan dan Pedesaan - Arum Lusiana; Suparmi Suparmi; Ulfah Musdalifah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
This research aims to know the difference in patient satisfaction based on four dimensions that are tangible, reliability, empathy, responsiveness and assurances against MCH services at BPJS programs in urban and rural health centers . Research design was quantitative research with cross sectional study. Total sample were 140 people consisting of 70 patients and 70 health centers Urban Rural health center patients . Data analysis used Mann Whitney U-test. The results showed that patient satisfaction is higher in rural areas than urban areas . For all dimensions of quality of rural health centers also obtain an average value higher than urban health centers. In conclusion, there are differences in the level of patient satisfaction and quality of MCH services at BPJS program in Urban and rural areas.